Mini-review on laser-induced nanoparticle heating and melting - Baimler, Ilya V.; Simakin, Alexander V.; Dorokhov, Alexey S.; Gudkov, Sergey V. (Frontiers in Chemistry, 2024)
The development of various nanomaterials production technologies has led to the possibility of producing nanoparticles (NPs) and nanostructures, which can find a wide range of applications, from the fabrication of microelectronic devices to the improvement of material properties and the treatment of cancer. The unique characteristics of nanoparticles are primarily due to their small size, which makes size control important in their preparation. Modification of nanoparticles by laser irradiation and obtaining desired nanoparticle properties is a promising approach because of its ease of implementation. The purpose of this review is to analyze the works devoted to the study of laserinduced heating and melting of nanoparticles, to collect information and evaluate the results of using this method for functionalization and modification of metallic nanoparticles, and to discuss promising directions for the use of this technique.